Daily migrations in a shifting landscape: Facilitating a circular economy on the south peninsula - Macarthur, Emma (School of Architecture, Planning and Geomatics, 2024)
The Noordhoek Valley encompasses the residential areas of Noordhoek, Masipumelele, Sun Valley, Ocean View and Kommetjie. The valley is emblematic of the challenges and opportunities present at South Africa's urban fringe. The valley is dominated by natural systems, with settlement pinched between fragments of a national park, and the dramatic topography of the mountains and ocean. As a resident of the area, I have noticed this sleepy corner of the greater Cape Town Metropolitan area move through the quiet desperation of the COVID-19 pandemic and into a highly desirable semi-gration destination. This residential boom is dramatically changing the social character of the communities and is revealing the spatial pressures this new density is placing on the sensitively balanced urban and natural systems. This research project investigates these pressures in an in-depth study of the valley. The project produces an intervention to lay the foundations for an adaptable framework plan to meet the demands of the coming developments. This is achieved through reaffirming and establishing spatial character through public space interventions. The project connects across planning divides through walkable perforations of hard urban divisions. It improves resilience through a network of safe public spaces within effective lighting and activation for around the clock utility. The project also provides dignified access to sanitation, waterpoints, educational and medical centres. These strategies develop a robust urban fabric, shifting the patchwork of spatial use from divided areas to an integrated form where new land use and intensification of existing commercial activities unlock the economic potential of the valley. This strategy of perforations to develop access and shifting edge conditions to facilitate active public space can be deployed throughout the valley to nurture the community's circular spatial, commercial and ecological economies.